Book Collections in Long Day Care: Do they Reflect Racial Diversity?. Issue 2 (June 2017) - Adam, Helen; Barratt-Pugh, Caroline; Haig, Yvonne
CHILDREN'S LITERATURE IS IMPORTANT because it nurtures emotional, social, creative and cognitive development, and gives children opportunities to appreciate and respond to diversity. In particular, literature that portrays racial and cultural diversity is a powerful means of promoting understanding of others while affirming individual identity. However, the limited number of studies about the nature and use of literature that reflects diversity in early childhood settings prompted this study, which investigates the nature of book collections in five long day care centres in the metropolitan region of Perth, Western Australia, with a specific focus on the extent to which they reflect racial diversity. Qualitative data was drawn from an audit of the children's book collections (2377 books) across each of the five centres. The findings revealed a lack of representation of racial diversity in those collections and where racial diversity was portrayed, non-dominant cultures were commonly misrepresented through stereotypical images often portraying outdated perspectives.